2004
DOI: 10.1002/ajh.20075
|View full text |Cite
|
Sign up to set email alerts
|

The older sickle cell patient

Abstract: The lifespan of sickle cell patients has increased substantially. We chose to compare the attributes of older sickle cell patients with younger ones within the confines of a single institutional study serving the local Bronx population. Laboratory and clinical assessments from 40 patients with sickle cell disease over 40 years of age were compared to 40 patients under 30 years of age. When the older group was compared to the younger group, hemoglobin, indirect bilirubin, and platelet counts were significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 24 publications
2
13
2
Order By: Relevance
“…Similarly, chronic renal disease, defined as an irreversible reduction in GFR, was quite frequent. These findings are consistent with prior reports of higher serum creatinine and lower GFR levels seen in older sickle cell patients (4). This in turn, compromises optimal care of these patients, including dose modifications or interruptions needed for certain medications such as iron chelating agents.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, chronic renal disease, defined as an irreversible reduction in GFR, was quite frequent. These findings are consistent with prior reports of higher serum creatinine and lower GFR levels seen in older sickle cell patients (4). This in turn, compromises optimal care of these patients, including dose modifications or interruptions needed for certain medications such as iron chelating agents.…”
Section: Discussionsupporting
confidence: 91%
“…It is not possible, however, to exclude that lower platelet counts could be associated with the presence of hepatitis C or older age, as already described in SCD [29,30]. Although our study evidenced older age in this subgroup of patients, no association with hepatitis C could be noted.…”
Section: Discussioncontrasting
confidence: 47%
“…While a single study found thrombocytosis to be associated with impaired cognitive dysfunction in children with SCD (74), epidemiological studies have not reported thrombocytosis to be associated with increased overall severity of SCD, (75)(76)(77)(78)(79)(80), although such studies did not consider platelet size or mass. Despite the evidence for increased platelet consumption during painful crises (9), there are few data to support a role for platelets in microvascular obstruction, and small studies of aspirin, aspirin with dipyridamole, and ticlopidine failed to show a definitive benefit in reducing the frequency of pain crises (20)(21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%